1991
DOI: 10.1002/nur.4770140606
|View full text |Cite
|
Sign up to set email alerts
|

Perceived stressors and coping responses in persons with recurrent genital herpes

Abstract: This descriptive study was designed to examine the disease experience of persons who have genital herpes by identifying the nature and frequency of disease-related stressors and coping responses associated with these stressors. Participants were 34 women and 26 men who were on average 5.3 years postdiagnosis, and experienced a mean of 6.4 recurrences per year. Respondents reported a wide range of disease-related stressors (M = 7). The category of stressors identified most often was related to disease consequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 15 publications
1
30
0
Order By: Relevance
“…Keeping secrets from strangers also resulted in increased depression in men. These findings are consistent with previous studies that report the lack of disclosure of one's diagnosis due to the stigma attached to this disease ( Keller et al, 1991; Swanson & Chenitz, 1993).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Keeping secrets from strangers also resulted in increased depression in men. These findings are consistent with previous studies that report the lack of disclosure of one's diagnosis due to the stigma attached to this disease ( Keller et al, 1991; Swanson & Chenitz, 1993).…”
Section: Discussionsupporting
confidence: 93%
“…Anger and hostility are mood states directed toward the person who gave them the disease ( Keller, Jadack, & Mims, 1991; Mindel, 1996; Swanson & Chenitz, 1993), and directed toward the health professional who diagnosed them (often following a series of misdiagnoses) ( Swanson & Chenitz, 1993). People diagnosed with genital herpes are often angry and have blamed themselves for contracting the disease ( Swanson & Chenitz, 1993).…”
Section: Review Of Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Although previous research has identified psychosocial morbidity associated with HSV-2, it has focused specifically on individuals with symptomatic recurrences. [4][5][6] Only one published quantitative study has explored the psychosocial impact of HSV-2 diagnosis in asymptomatic individuals. 7 The current study was designed to assess qualitatively emotional and psychosocial responses to a diagnosis of HSV-2 infection based on results of a serological test in asymptomatic individuals and to provide a framework for counselling delivered in clinical settings.…”
mentioning
confidence: 99%
“…The biopsychosocial burden often experienced by people living with symptomatic genital herpes has been well documented ( Keller et al 1991, Swanson & Chenitz 1993, Mindel 1996, Peto & Juel‐Jensen 1996). To alleviate the physical and psychological pain and to improve quality of life, early studies examined psycho‐social support for individuals ( Gould & Tissler 1984), couples ( Drob & Bernard 1985) and groups ( Drob & Bernard 1986, Longo et al 1988 , McLarnon & Kaloupek 1988).…”
Section: Introductionmentioning
confidence: 99%